Does marriage and having children make life better in Europe? - Ainsaar, Mare; Rootalu, Kadri (Studies of Transition States and Societies, 2015)
The diversity of family types is increasing in Europe. Existing research provides inconsistent results on whether having children in a family influences life satisfaction, and even less is known about how different partnership and social support types influence life satisfaction. We investigate the life satisfaction of officially registered and cohabiting persons with and without children in 24 European countries using the latest European Social Survey data from 2012. To investigate the influence of society and individual selection on family types, we include a range of individual and macroeconomic indicators in the multilevel analyses. The results demonstrate that life satisfaction is influenced by partnership and partnership type, children in a household do not elevate life satisfaction, and lack of economic coping problems might raise the positive value of children. Although the general life satisfaction levels follow predominantly the East–West alignment, the life satisfaction of families within countries is more driven by social support and a clear division of countries between East and West societies is not perceivable.